THE STATE LANGUAGE POLICY AND ITS INFLUENCE ON ETHNIC MINORITIES’ EMPLOYMENT AND EDUCATION OPPORTUNITIES - Kakenova, Aizhan (Nazarbayev University School of Sciences and Humanities, 2017)
In this thesis, I investigate the effect of the state language policy on the ethnic minorities’ opportunities in regards to their education and employment. My study demonstrates that one of the effects of the state language policy is a rising number of the Kazakh-language speaking population in society. Ethnic minorities argue that fluency in the state language positively contributes to their well-being. There are ethnic minorities who face significant obstacles in getting a job due to lack of fluency in the state language and they acknowledge the importance of the state language on their socio-economic success in Kazakhstan. Another effect of the Kazakhization law is on ethnic minorities’ education. Ethnic minority parents understand that proficiency in the state language will contribute to future success of their children.
ЯЗЫКОВАЯ ПОЛИТИКА И ЕГО ЭФФЕКТ НА РАБОЧИЕ И ОБРАЗОВАТЕЛЬНЫЕ ВОЗМОЖНОСТИ ЭТНИЧЕСКИХ МЕНЬШИНСТВ
ТІЛ САЯСАТЫ ЖӘНЕ ОНЫҢ ЭТНИКАЛЫҚ ТОПТАРДЫҢ ЖҰМЫС ПЕН ОҚУ МҮМКІНДІКТЕРІНЕ ӘСЕРІ